(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Russia’s national goals and strategic tasks for the period up to 2024 can be implemented under the condition of the dynamic development of all the country’s territories, including its most numerous level—a municipal level. Starting conditions of the entities of the Russian Federation and the municipalities differ substantially, which will objectively tell on their involvement in the national project implementation and a possibility of solving severe socio-economic problems. The research argues that it is necessary to differentiate the scales and tools of the state regulation of the municipal formations development in accordance with the territory typology that takes into account a potential, problems, and a level of the reached social, economic, and environmental development. The research offers a system of indicators and an approach to the integrated assessment in terms of a level and sustainability of development of the municipalities, which was tested by the example of the Republic of Mordovia. The research substantiates types of municipal formations of the republic and goals and tools of the regional policies.